Adobe Lightroom CC and Photoshop CC for photographers - Snider, Lesa (Classroom in a book, the official training workbook from Adobe Systems, 2017)
"The fastest, easiest, most comprehensive way to learn Adobe Lightroom in conjunction with Adobe Photoshop. Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program doesan official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts, "--